A Paradigm Shift in Unemployment Based on the Role of Business Ownership: Ghana as Case - Abredu , Pearl; Li, Cai; Essien, Frank Kofi (International Journal of Management Innovation Systems, 2024)
Both researchers and policymakers have given the relationship between entrepreneurship and unemployment a lot of thought. The changes in the area of unemployment in the country has caused many people to move into owning their businesses. This activity has initiated a relief to the government since its responsibility is to create lucrative jobs to its citizens. This paper seeks to address the paradigm shift in unemployment in Ghana, the role of business ownership. The study explained the determinants of unemployment, and the entrepreneurship drive to unravel unemployment in the country. Using a cross-sectional dataset, the study focused on Ghana’s economic growth as well as the country’s unemployment rate. Using an online survey of 400 respondents and data from the Ghana Statistical Service (GSS) and the Global Entrepreneurship Monitor dataset as its key element in addressing the usefulness of the study. The researcher investigated a paradigm shift in unemployment using the SPSS tool (version 23.0) and regression for the data analysis. With a Cronbach Alpha of 0.898 which explains the reliability statistics of the study variables, the research result shows that at a coefficient of 0.73, Business ownership will have an aid to employment rate with a highly significant P-value of 0.000. Recommendation from the study is that Policymakers should investigate and assess the elements that influence entrepreneurship by placing reduction on the interest put on loan offered to young entrepreneurs.